Personalised risk prediction following emergency department assessment for syncope. Issue 7 (5th November 2021) - Thiruganasambandamoorthy, Venkatesh; Yan, Justin W; Rowe, Brian H; Mercier, Éric; Le Sage, Natalie; Hegdekar, Mona; Finlayson, Anne; Huang, Paul; Mohammad, Hassan; Mukarram, Muhammad; Nguyen, Phuong Anh (Iris); Syed, Shahbaz; et al.
Abstract : Background: Published risk tools do not provide possible management options for syncope in the emergency department (ED). Using the 30-day observed risk estimates based on the Canadian Syncope Risk Score (CSRS), we developed personalised risk prediction to guide management decisions. Methods: We pooled previously reported data from two large cohort studies, the CSRS derivation and validation cohorts, that prospectively enrolled adults (≥16 years) with syncope at 11 Canadian EDs between 2010 and 2018. Using this larger cohort, we calculated the CSRS calibration and discrimination, and determined with greater precision than in previous studies the 30-day risk of adjudicated serious outcomes not identified during the index ED evaluation depending on the CSRS and the risk category. Based on these findings, we developed an on-line calculator and pictorial decision aids. Results: 8233 patients were included of whom 295 (3.6%, 95% CI 3.2% to 4.0%) experienced 30-day serious outcomes. The calibration slope was 1.0, and the area under the curve was 0.88 (95% CI 0.87 to 0.91). The observed risk increased from 0.3% (95% CI 0.2% to 0.5%) in the very-low-risk group (CSRS −3 to –2) to 42.7% (95% CI 35.0% to 50.7%), in the very-high-risk (CSRS≥+6) group (Cochrane-Armitage trend test p<0.001). Among the very-low and low-risk patients (score −3 to 0), ≤1.0% had any serious outcome, there was one death due to sepsis and none suffered a ventricular arrhythmia. Among the medium-risk patients (score +1 to+3), 7.8% had serious outcomes, with <1% death, and a serious outcome was present in >20% of high/very-high-risk patients (score +4 to+11) including 4%–6% deaths. The online calculator and the pictorial aids can be found at: https://teamvenk.com/csrs Conclusions: 30-day observed risk estimates from a large cohort of patients can be obtained for management decision-making. Our work suggests very-low-risk and low-risk patients may be discharged, discussion with patients regarding investigations and disposition are needed for medium-risk patients, and high-risk patients should be hospitalised. The online calculator, accompanied by pictorial decision aids for the CSRS, may assist in discussion with patients.